Pembuatan Storyboard Iklan Layanan Masyarakat Dampak Negatif Gawai Dalam Pola Asuh Orang Tua Terhadap Anak - Rima Karmelia Fernanda; Diana Aqidatun Nisa; Alfian Candra Ayuswantana (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
A The storyboard for this public service advertisement aims to design a visual representation of the negative impact of excessive gadget use on parenting styles. To analyze this issue, the researcher uses a qualitative approach to gain a deeper understanding of the phenomenon, particularly the interactions between parents and children in the digital age. In the design phase, the researcher applies the design thinking method to create an effective storyboard, focusing on planning each scene in detail. This process begins with analyzing relevant literature and observing parent-child interactions, which forms the basis for crafting the message to be conveyed. The main message in this storyboard is the importance of balancing technology use with direct interaction between parents and children. The resulting storyboard presents engaging visuals and clear narration, aiming to make the message accessible to a wide audience. It is hoped that the results of this research will contribute to parenting campaigns in the digital era and serve as a reference for policymakers, education practitioners, and the general public in creating a better environment for children's development.